2014
DOI: 10.1097/qad.0000000000000507
|View full text |Cite
|
Sign up to set email alerts
|

The relationship of physical performance with HIV disease and mortality

Abstract: Objective To evaluate whether HIV infection was associated with reduced physical performance, and to examine if reduced physical performance predicted mortality in our aging cohort of HIV-infected and HIV-uninfected persons. Design Prospective, observational cohort of current and former injection drug users in the AIDS Linked to the IntraVenous Experience study in Baltimore, Maryland, USA. Methods The Short Physical Performance Battery (SPPB) was used as an objective measure of physical performance and mea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
56
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 74 publications
(60 citation statements)
references
References 37 publications
4
56
0
Order By: Relevance
“…A typical 65-year-old lives with two or more chronic conditions[23]. The addition of chronic HIV infection to this disease burden adds another layer of complexity to an aging system, which may hasten the onset of functional decline, aggravating the risk of future disability and death[2, 3]. Further, our results suggest a strong psychosocial component to rate of decline in grip strength, as demonstrated by the significant contributions of race and education.…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…A typical 65-year-old lives with two or more chronic conditions[23]. The addition of chronic HIV infection to this disease burden adds another layer of complexity to an aging system, which may hasten the onset of functional decline, aggravating the risk of future disability and death[2, 3]. Further, our results suggest a strong psychosocial component to rate of decline in grip strength, as demonstrated by the significant contributions of race and education.…”
Section: Discussionmentioning
confidence: 76%
“…Although a link between reduced functional performance and HIV infection has been hypothesized, the majority of previous research has focused on the syndrome of frailty[25, 26], aerobic capacity[27], or composite measures of performance[3]. Moreover, previous research limited to differences in grip strength by HIV serostatus has been cross sectional, focused on participants with lipodystrophy, or largely inconclusive[12, 13, 28], leaving the possibility of differences in the rate of strength decline undefined.…”
Section: Discussionmentioning
confidence: 99%
“…Another possible limitation is the use of self-reported functional status, as self-report of functional status may be predictive of outcomes such as mortality in HIV-negative populations, 37 but only objective measures of physical function have been studied with outcomes in HIV-positive populations. 10,11 Although we included adherence to antiretroviral medications and the association between polypharmacy and age, we did not examine adherence to other chronic medications or perform a more detailed evaluation of types of other chronic medications, both of which are important issue for the aging HIV-positive population. While our findings add support to current guidelines recommending integration of geriatric and HIV medicine principles, 38 next steps should include developing interventions to address the complex medical needs we found and understanding if the same interventions designed to work in older HIV negative populations have utility for the aging HIV population.…”
Section: Discussionmentioning
confidence: 99%
“…10-12 Utilizing geriatric assessments in combination with traditional HIV assessments in HIV care settings could help providers address the medical complexity experienced by older HIV-infected adults and identify the most vulnerable patients in need of additional intervention. Other tools such as the Veterans Aging Cohort Study (VACS) Index, a prognostic tool based on both HIV and comorbid condition markers, can also be used to identify adults at the highest risk of morbidity and mortality.…”
Section: Introductionmentioning
confidence: 99%
“…This study found that expression of the Fried FP did indeed predict mortality in this cohort of IDUs. Recently, another study from the ALIVE cohort found that poor physical function, as assessed by the short physical performance battery (SPPB) was also an independent predictor of mortality (42). In addition, data from the Veterans Aging Cohort Study (VACS) showed that an adapted frailty-related phenotype was predictive for hospitalization and mortality in aging HIV-infected veterans (6).…”
Section: Aging and Frailty In Hiv-infected Populationsmentioning
confidence: 99%